The developing exercise dance patterns that affect body fat mass for staff and students with overnutrition at Thailand National Sports University, Yala Campus - Mayakul, Siriporn; Keawyok, Kridsada; Jodnak, Supavadee (Health Science, Science and Technology Reviews, 2025)
The aim of this research is to develop an exercise dance pattern that reduces body fat mass for staff and students with nutritional excess at the Yala Campus of the National Sports University. The study also compares the outcomes before and after implementing the dance pattern and evaluates the participants’ satisfaction with them. Thirty participants were students from the Faculty of Sports Science and Health and staff from the National Sports University, Yala Campus, who had overnutrition condition with a body mass index (BMI) greater than 23.0 kg/m². and aged between 18–59 years, regardless of gender. The research tools included the exercise dance pattern comprising 15 movements, the dietary behavior questionnaire, and the satisfaction survey on the exercise dance, which experts validated for reliability and validity. These tools are suitable for use in exercise programs designed for individuals with overweight conditions. Participants practiced the exercise dance pattern for 8 weeks, three times a week, 40 minutes per session. A single-group pretest-posttest design was applied, with paired t-tests used for statistical analysis at a significance level of p .05. The results showed significant reductions in weight, BMI, body fat mass, fat percentage, and visceral fat among the participants after the 8-week intervention compared to baseline measurements, with statistical significance at the .05 level. Additionally, muscle mass significantly increased (p < .05). The overall satisfaction with the exercise dance pattern was rated at the highest level, with an average score of 4.61. Participants expressed high satisfaction with the exercise dance’s alignment with music rhythm, its enjoyable nature, and its applicability for exercise among individuals with overweight.